Preparation of Ammonia Dealuminated Metakaolinite and Its Adsorption against Bixin - Winda Rahmalia; Jean-Francois Fabre; Thamrin Usman; Zéphirin Mouloungui (Universitas Gadjah Mada, 2020)
This study aims to prepare dealuminated metakaolinite which has a high surface area by using NH4OH as an activator. The natural kaolinite sample was treated at 600 °C for 6 h in order to obtain metakaolinite. A dealuminated metakaolinite was then prepared by the repeated activation method using concentrated ammonia (5 M NH4OH) at room temperature. Depending on the nature of each type of material, natural kaolinite, NH4OH treated kaolinite, metakaolinite and NH4OH treated metakaolinite were characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy-energy dispersive spectroscopy (SEM-EDS), and Brunauer-Emmett-Teller (BET-N2) measurements. XRD and FTIR results confirmed that structural transformation from kaolinite to metakaolinite had occurred. According to SEM-EDS data, the activation of metakaolinite by NH4OH allowed the dealumination of metakaolinite. The increase in the Si/Al ratio was almost twice as high as in kaolinite. BET-N2 analysis showed that the specific surface area and the total pore volume increased significantly after activation. Its adsorption properties were tested against bixin. Bixin adsorption on dealuminated metakaolinite followed pseudo-second order kinetic where k2 = 0.20 g/mg min. The adsorption isotherm followed the Langmuir model where qm = 0.72 mg/g.